PERBAIKAN SISTEM HUKUM INDONESIA MENUJU NEGARA HUKUM YANG BERKEADILAN - Mudemar A Rasyidi (JURNAL MITRA MANAJEMEN, 2019)
Pancasila as the foundation of the state, and the way of view of the Indonesian nation and Pancasila as philosophy of Indonesia nation, and also as the ideology of the Unitary State Republic of Indonesia, should be able to be practiced consitently, in creative and dynamic manner by all walks of life of communities, in creative and dynamic manner by all walks of life of communities, and groups living and existing in the Indonesian society.Being increasingly consistent, creative and dynamic the Pancasila is to be observed to in reality of life, both by the state officials and the people, then the life of nation and state also would be better, professional then Indonesia will be move developed in order to achieve a just and prosperous society. Furthermore, if Indonesia nation increasingly deepens and comprehend and practice it in a pure and consequence manner, as well as adhering to the 1945 Constitution and all provisions, regulations as well as other legislations enforced in Indonesia the all of them would be very determining in carrying out the improvement in Indonesian Legal system towards a legal state with justice adjusted to the modern science and technology advancements.